2008
DOI: 10.1016/j.jvs.2008.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Infrapopliteal angioplasty for critical limb ischemia: Relation of TransAtlantic InterSociety Consensus class to outcome in 176 limbs

Abstract: Infrapopliteal angioplasty is a reasonable primary treatment for CLI patients with TASC A, B, or C lesions. Restenosis, reintervention, or amputation was higher in patients who were unsuitable candidates for bypass; however, an attempt at PTA may be indicated as an alternative to primary amputation. Although restenosis, reintervention, or amputation is high after tibial angioplasty for CLI, excellent limb salvage rates may be obtained with careful follow-up and reinterventions when necessary, including bypass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
131
4
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(152 citation statements)
references
References 30 publications
10
131
4
7
Order By: Relevance
“…Despite the overall complexity of treated lesions in our series, the overall limb salvage at 1 and 3 years following conventional PTA is comparable to other published results and to outcomes from surgical bypass with a relatively low secondary reintervention rate of 15% (2)(3)(4)(5)(7)(8)(9)(10)(11)(12)(13)(14)(15). Although newer technologies such as drug-coated angioplasty balloons (DCB) or drug-eluting stents (DES), and atherectomy devices were absent in our series, there has been recent interest in the use of DCB and DES in the treatment of infrapopliteal lesions (16)(17)(18)(19)(20).…”
Section: Main Pointssupporting
confidence: 83%
See 3 more Smart Citations
“…Despite the overall complexity of treated lesions in our series, the overall limb salvage at 1 and 3 years following conventional PTA is comparable to other published results and to outcomes from surgical bypass with a relatively low secondary reintervention rate of 15% (2)(3)(4)(5)(7)(8)(9)(10)(11)(12)(13)(14)(15). Although newer technologies such as drug-coated angioplasty balloons (DCB) or drug-eluting stents (DES), and atherectomy devices were absent in our series, there has been recent interest in the use of DCB and DES in the treatment of infrapopliteal lesions (16)(17)(18)(19)(20).…”
Section: Main Pointssupporting
confidence: 83%
“…Technical success for the remaining A-C lesions was higher at 81% but is still lower than success rates previously reported (4,7). This is also consistent with the more conservative shift of categorizing longer stenotic lesions >10 cm as TASC C using the updated classification, which would have previously been regarded as TASC D. Therefore, the updated TASC categories represent a very different cohort of patients to those previously reported in the literature and the differences are particularly marked in the more advanced C and D categories.…”
Section: Main Pointscontrasting
confidence: 74%
See 2 more Smart Citations
“…One study has demonstrated that infrapopliteal angioplasty is a reasonable primary treatment for critical limb ischemia patients with TransAtlantic InterSociety Consensus (TASC) A, B, or C lesions. 4 Due to the multilevel nature of peripheral arterial disease, iliac or femoral lesions accompanied by the femoral artery bifurcation (FB) disease are frequently observed. 5,6 Endovascular surgery is poorly suited to treating lesions in the FB because they are bulky and eccentric.…”
mentioning
confidence: 99%